Systematic literature review of Family Business Sucession Planning : challenges and success factors - Guliyev, Heydar; Kubíček, Aleš; Machek, Ondřej, 1985-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
One of the most frequently discussed subjects in the field of family business, succession planning is a major concern for family businesses often filled with complexities in transferring leadership across generations. This bachelor's thesis presents a comprehensive overview of the issues and success factors in family business succession planning, drawing on insights from 20 studies published over the last two decades. Based on identifications of challenges and success factors, a theoretical framework named Integrated Succession Planning Model (ISPM) was developed that can serve as a practical tool for effective leadership transitions. This study not only identifies key factors affecting the succession process both negatively and positively, but also offers suggestions for further research and offers practical recommendations that can be useful for family business owners, business advisors and policymakers.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses